Sustainable agriculture of Serbia through the prism of the renewable energy sources market - Parušić Vesna; Kljajić Nataša; Grujić-Vučkovski Biljana (Trendovi u Poslovanju)
The agricultural sector significantly endangers the environment and human health through the excessive use of chemical agents and the use of heavy machinery. At the same time, the sector represents a significant source of renewable energy sources (abbreviated RES). The research results indicated that Serbia still does not have indicators for measuring RES production and consumption in the agricultural sector. Their determination should be the first task of public policies and national statistics, so that the state of the RES market in this sector can be effectively monitored. The research was enriched with a case study that examined the state of the domestic agropellet market and the possibilities of new producers entering this market. The results showed that, although the potential of agricultural biomass for the production of agropellets in Serbia is huge, the market for this energy source is quite underdeveloped. The awareness of the inhabitants of rural areas about the possibilities of using agricultural biomass for household energy needs is low, and an additional limitation is the non-incentive tax policy in this area.